Penguatan Profil Pelajar Pancasila bagi guru SD Sindanglaya melalui pendampingan implementasi Multicultural Fairtale - Wardhani, Prayuningtyas; Yarmi, Gusti (Universitas Hamzanwadi, 2023)
The implementation of the Pancasila Student Profile in Indonesian education is an initiative aimed at producing competent learners with strong character and behavior in line with Pancasila values. This profile is designed to prepare democratic, productive learners capable of facing global challenges in the 21st century. The goal of this mentoring program is to integrate Pancasila values into basic education through the implementation of Multicultural Fairytales at SD Sindanglaya, Garut, West Java. The program is structured to strengthen the Pancasila Student Profile, encompassing six character dimensions vital for lifelong competent and characterful learners. Utilizing a project-based learning approach, the program facilitates a holistic and contextual learning experience for teachers and students. During the implementation, from July 31 to August 3, 2023, 20 elementary school teachers participated in a series of planned activities, including field observation, training, and evaluation. The evaluation showed a substantial increase in the understanding of the Multicultural Fairytale concept, from 15% in the initial evaluation to 85% in the process evaluation, and finally to 90% in the final evaluation. This indicates the program's effectiveness in enhancing literacy and pedagogical competencies among teachers. The program also successfully sparked high motivation and enthusiasm among teachers, reflected in full attendance and a strong commitment to quality, engaging learning for students. These results affirm the importance of reinforcing a Pancasila-oriented student profile, focusing not only on cognitive achievement but also on character and attitude development. This mentoring program has made a significant contribution to the professional development of teachers and the improvement of learning quality, in line with Indonesia's educational needs in facing global challenges in the era of Industry 4.0.